Perceptions of First-Generation Canadians on Rights and Deservingness of Healthcare for Canadian Newcomers - Doreleyers, April Elizabeth (Université d'Ottawa / University of Ottawa, 2019)
The present thesis provides insight into the social context in which the perceptions that first-generation Canadians have towards access to healthcare for newcomers may emerge. The study was completed in Ottawa-Gatineau in March and April of 2016 and covered the perspectives of nine people, across eight semi-structured interviews. Following the review of the literature and theoretical framework, the present work highlights the role that first-generation Canadians’ moral worlds play into how they perceive access to healthcare for Canadian newcomers. On the subject of perceptions of first-generation Canadians, this research goes beyond the practical concerns faced by newcomers and delves into people’s moralities as these relate to the interpretation of rights and deservingness of access to subsidized healthcare. In grasping the different ways that health and healthcare are understood, as well as individual perceptions of the granting healthcare to newcomers to Canada, my thesis makes visible moral elements that can help to understand how rights to healthcare can be configured and reconfigured across various contexts.
Keywords: Right; Deservingness; Morality; Moral economies; Moral communities; Healthcare